Effects of training periodization on cardiac autonomic modulation and endogenous stress markers in volleyball players - Mazon, J.; Gastaldi, A.; Di Sacco, T.; Cozza, I.; Dutra, S.; Souza, H. (Scandinavian Journal of Medicine & Science in Sports, 2013)
We investigated the effects of selective loads of periodization model (SLPM) on autonomic modulation of heart rate variability (HRV) and endogenous stress markers before and after a competition period in volleyball players (N=32). The experimental protocol for the evaluation of HRV consisted of using spectral analysis of time series composed of the R-R intervals derived from electrocardiogram obtained in the supine position and during the tilt test. Stress marker levels were determined by quantifying the plasma concentration of endogenous catecholamines, cortisol and free testosterone. The results showed no changes between the levels of HRV before and after a competition period. In contrast, the quantification of the plasma concentration of endogenous stress markers revealed reductions in the levels of total catecholamines, noradrenaline and cortisol. These changes were accompanied by increases in the concentration of free testosterone and in the testosterone/cortisol ratio. In conclusion, our results demonstrate that the SLPM did not change the cardiac autonomic modulation of HRV, but promoted beneficial adaptations in athletes, including positive changes in the plasma concentration of the endogenous stress markers. The absence of changes in HRV indicates that there is no direct relationship between cardiac autonomic modulation and endogenous stress markers in the present study.